2015
DOI: 10.3928/23258160-20150909-09
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab Versus Ranibizumab in the Treatment of Macular Edema Due to Retinal Vein Occlusion: 6-Month Results of the CRAVE Study

Abstract: In the treatment of retinal vein occlusion, bevacizumab and ranibizumab have similar effects on reducing macular thickness and improving visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 14 publications
3
10
0
2
Order By: Relevance
“…Our results are in line with other real-world studies, which have shown that, in patients with RVO, and as early as at 2 weeks postinjection, CMT reduction is higher with ranibizumab compared to bevacizumab (10). Two prospective trials comparing bevacizumab and ranibizumab in the treatment of RVO (11) or BRVO (12) concluded that both agents had similar effects in reducing macular thickness and improving visual acuity at 6 months (11), even using a PRN regimen, with a mean number of injections of bevacizumab and ranibizumab of 3.2 and 3.0, respectively (12). Therefore, both bevacizumab and ranibizumab are effective, even with real-world treatment regimens using a lower number of injections than recommended.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are in line with other real-world studies, which have shown that, in patients with RVO, and as early as at 2 weeks postinjection, CMT reduction is higher with ranibizumab compared to bevacizumab (10). Two prospective trials comparing bevacizumab and ranibizumab in the treatment of RVO (11) or BRVO (12) concluded that both agents had similar effects in reducing macular thickness and improving visual acuity at 6 months (11), even using a PRN regimen, with a mean number of injections of bevacizumab and ranibizumab of 3.2 and 3.0, respectively (12). Therefore, both bevacizumab and ranibizumab are effective, even with real-world treatment regimens using a lower number of injections than recommended.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of patients were treated with the same anti-VEGF agent throughout the study period, but in one-third of the patients, the type of anti-VEGF used was switched at least once, usually from ranibizumab to bevacizumab. The reasons for switching between anti-VEGF therapies were not collected, but as controlled clinical studies 21 , 22 and retrospective case series studies 23 , 24 have suggested that ranibizumab and bevacizumab are similarly effective in the treatment of patients with RVO, and bevacizumab is available at substantially lower cost, 25 patients may have switched from ranibizumab to bevacizumab for cost savings.…”
Section: Discussionmentioning
confidence: 99%
“…Rajagopal et al [15] in CRAVE study (Bevacizumab vs Ranibizumab in the treatment of macular edema due to retinal vein occlusion) compared efficacy of monthly ranbizumab or bevacizumab for RVO-ME in a randomised clinical traal. After six months, changes in central macular thickness and visual acuity were not different between the treatment groups.…”
Section: Discussionmentioning
confidence: 99%